2015
DOI: 10.3354/esr00682
|View full text |Cite
|
Sign up to set email alerts
|

Movements and survival of juvenile reddish egrets Egretta rufescens on the Gulf of Mexico coast

Abstract: Understanding natal dispersal patterns of animals is critical to development of effective species conservation plans, as it ensures that population management takes place at appropriate scales. The reddish egret Egretta rufescens is a threatened waterbird species lacking documentation on many aspects of its ecology, including movement behaviors at all life stages. We attached satellite transmitters to 25 juvenile reddish egrets on their natal colonies and observed their dispersal patterns and subsequent moveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 45 publications
(41 reference statements)
1
16
0
Order By: Relevance
“…Bates et al (2015) estimated juvenile survival of reddish egrets at 78% for the first 6 mo after hatch. Geary et al (2015) found similar results for the first 6 mo after hatch at 83%; yet survival decreased to 53% by 17 mo after hatch.…”
Section: Discussionsupporting
confidence: 62%
“…Bates et al (2015) estimated juvenile survival of reddish egrets at 78% for the first 6 mo after hatch. Geary et al (2015) found similar results for the first 6 mo after hatch at 83%; yet survival decreased to 53% by 17 mo after hatch.…”
Section: Discussionsupporting
confidence: 62%
“…Furthermore, we performed 2–3 replicate amplifications for each sample, and results were consistent among tissues from the same individual. Previous studies of reddish egrets have reported skewed sex ratios in small samples of hatch‐year and adult birds (Geary et al , Koczur et al ), which may be due in part to the timing or methods of capture. In addition, these carcasses represent mortalities, which may indicate sex‐bias in survival.…”
Section: Discussionmentioning
confidence: 96%
“…Recent reductions in the mass of satellite transmitters and advances in other technology (e.g. light-level geolocators, McKinnon et al 2013) have made it more feasible to study movements of juveniles (Bridge et al 2011, Margalida et al 2013, Geary et al 2015, Flack et al 2016, Harel et al 2016. As a result, several studies have demonstrated differences in the foraging patterns of juveniles vs. adults (Riotte-Lambert & Weimerskirch 2013, Weimerskirch et al 2014, de Grissac et al 2017).…”
mentioning
confidence: 99%